NATURAL FACTOR OF MENTALITY FORMATION - E. A. Magomedov (Юг России: экология, развитие, 2014)
The article says about mentality and its factors. Especial attentions is paid the biological and natural factors as nature is a factor always existing and natural parameters form ethnos along side with history and mentality.